2018
DOI: 10.1080/13554794.2018.1492729
|View full text |Cite
|
Sign up to set email alerts
|

A new MAPT deletion in a case of speech apraxia leading to corticobasal syndrome

Abstract: Speech apraxia is a disorder of speech motor planning/programming leading to slow rate, articulatory distortion, and distorted sound substitutions. We describe the clinical profile evolution of a patient presenting with slowly progressive isolated speech apraxia that eventually led to the diagnosis of corticobasal syndrome (CBS), supporting the evidence that this rare speech disorder can be the first presentation of CBS. Moreover, we found a novel variant in MAPT gene, which is hypothesized to be disease-causi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Tau's role in LTD appears to depend on its phosphorylation at serine 396 permitting AMPA receptor internalisation [218]. Crucially, a number of studies have reported human genetic cases of FTD [199,294] or intellectual disability [172,232,263] in which tau levels are drastically reduced compared to age-matched controls. Reduced soluble tau has also been reported in normal ageing [187], Parkinson's disease (PD) [145], and AD [137,191] (potentially due to sequestration of tau into NFTs).…”
Section: Tau In Ltp Ltd and Memorymentioning
confidence: 99%
“…Tau's role in LTD appears to depend on its phosphorylation at serine 396 permitting AMPA receptor internalisation [218]. Crucially, a number of studies have reported human genetic cases of FTD [199,294] or intellectual disability [172,232,263] in which tau levels are drastically reduced compared to age-matched controls. Reduced soluble tau has also been reported in normal ageing [187], Parkinson's disease (PD) [145], and AD [137,191] (potentially due to sequestration of tau into NFTs).…”
Section: Tau In Ltp Ltd and Memorymentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30][31][32][33][34] In two (5.71%) studies, the language impairments were not described in detail. [26][27][28][29][30][31][32][33][34][35] The remaining studies mentioned a variety of different symptoms, including agraphia 15,23,31,[36][37][38][39] speech apraxia, 2,23,36,37,39,40 dysarthria, 36,41 a mixed type of PPA, 16 logopenic variant of PPA (L-PPA), 15,21 anomic aphasia, 3,4,42 transcortical motor aphasia 42 and Broca's aphasia. 42 The tests used for assessment and classification of type of evaluation are also given in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…4,12,35,40,41 The assessment of methodological quality of the manuscripts is shown in Table 2. Ten studies (28.57%) were classified as "high quality", 2,13,14,16,[20][21][22][23]36,39 23 (65.71%) as "moderate quality", 3,4,15,[24][25][26][27][28][29][30][31][32][33][34][35]37,38,[40][41][42]47,50,51 and two (5.71%) as "low quality". 12,45 GRADE CERQual analysis was carried out for three separate review findings: comprehensive language impairments, impairment in isolated language processing, and absence of language impairment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations